Molecular biology of cancer - F Macdonald (Bios Scientific, 1997)
This book provides a detailed overview of the processes which lead to the development and proliferation of cancer cells, including the techniques available for their study. It also describes the means by which tumor suppressor genes and oncogenes may be used in the diagnosis and in determining the prognosis of a wide variety of cancers, including breast, genitourinary, lung and gastrointestinal cancer. Other relevant groups of genes are also discussed, such as the DNA mismatch repair genes which have a role in colon cancer, and the cyclins